Web Data Scraper Tools: Survey - Nain, Sneh; Lall, Bhumika (International Journal of Computer Sciences and Engineering, 2014)
World Wide Web contains a huge amount of information that is increasing rapidly. Usually data stored on the web are in unstructured and semi-structured form. In order to obtain the essential data from the web, certain data scraper tools had been invented. In this paper we intend to briefly survey Web Data Scraper Process, the taxonomy for characterizing Web Data Scraper Tools and provide qualitative analysis of them. Hopefully, this work will simulate other studies aimed at a more comprehensive analysis of data scraper approaches and tools for Web data.